SAT-391 Perioperative Glucocorticoid Therapy for Patients with Adrenal Insufficiency: Dosing Based on Hydrocortisone Pharmacokinetic Data - Rahhal, Marie-Noel (J Endocr Soc, 2019)
Background: Perioperative hydrocortisone (HC) therapy for patients with adrenal insufficiency (AI) vary from one institution to another and recommendations are not based on definitive data. Although the necessary HC dose is unknown, we utilized recent data documenting normal periop HPA function(1) as a guide to assess HC substitution therapy in patients with AI. Goals: Examine the impact of 2 HC regimens on clinical symptoms and serum cortisol levels in subjects with documented AI, receiving chronic physiologic replacement. Methods: HC was administered for 48 hrs to 145 subjects with AI (37 with primary and 108 had central disease) undergoing surgical procedures (abdomen/ pelvis/ chest/ ortho) requiring general anesthesia. Oral HC (20 mg) was given 2-3 hrs before while IV therapy was started at intubation. Two regimens were randomly tested in patients with similar demographics and similar surgical procedures. One group (n=77) received 15mg HC every 6 hrs for 24 hours then dosing was adjusted as clinically necessary. A second group (n=68) received 25mg HC every 6 hrs for 24 hrs followed by 15 mg every 6 hrs for 24 hrs. Cortisol levels were determined frequently after the first and second HC injections during the first 24 hrs and at 36 and 48 hrs in the second groups. Results: There were no clinical evidence of AI during the peri-op period and all were discharged home. Baseline cortisol levels were 16.1±4.9 ug/dL. One hr after the first 15 and 25 mg HC doses, cortisol levels were 38.9±6.7 and 65.4±14 ug/dL, respectively (P<0.001). Nadir cortisol levels at 6 hrs in these patients were 10.8±4 and 19.9±5.5 ug/dL (P<0.001) respectively. The nadir serum cortisol levels after the second HC dose (13.8±3 VS 26.7±5 ug/dL) were higher (<0.01) than those obtained after the first dose. Patients receiving 15 mg HC had cortisol levels always >7.8 ug/dL while those who received 25 mg had levels >11.9 ug/dL. Both HC regimens resulted in cortisol levels that fell within, and were often higher than those observed in subjects with normal HPA. The calculated cortisol t1/2 after the first 25 mg dose (3.1±0.3 hrs) was higher (P<0.01) than that obtained after the 15 mg (2.6± 0.4 hrs) dose. Similarly, for both HC doses, cortisol t1/2 after the second dose was slightly higher than that determined after the first dose (P<0.01). Summary and Conclusions: A HC dose of 20 mg orally followed by 15 mg IV every 6 hrs is sufficient to raise serum cortisol levels in patients with AI to levels similar to those observed in subjects with normal HPA function. The 25 mg every 6 hrs dose may be of help in patients with prolonged and more extensive surgical procedures. A HC regimen of 25 mg every 6 hrs for 24 hrs followed by 15 mg every 6 hrs resulted in cortisol levels that are consistently similar or above those observed in critically-ill subjects. The data calls into question the current practice of using excessive peri-op doses of HC.References 1. El Sibai K, et al Endocrine 58:134